Effect of vonoprazan on the treatment of artificial gastric ulcers after endoscopic submucosal dissection: Prospective randomized controlled trial. Issue 5 (5th April 2017) - Tsuchiya, Izumi; Kato, Yuri; Tanida, Emiko; Masui, Yoshifumi; Kato, Shingo; Nakajima, Atsushi; Izumi, Motoyoshi
Abstract : Background and Aim: Proton pump inhibitors are effective for the treatment of gastric ulcers after endoscopic submucosal dissection (ESD). However, the most excellent therapy is controversial. Vonoprazan, an active potassium‐competitive acid blocker, has a strong gastric acid secretion inhibitory effect, but its efficacy for the treatment of post‐ESD gastric ulcers is unclear. Herein, we aimed to determine the healing effect of vonoprazan on post‐ESD gastric ulcers. Methods: We carried out a prospective randomized controlled trial examining 92 patients who had undergone ESD for the treatment of gastric neoplasms between April 2015 and June 2016 at Machida Municipal Hospital. Patients were treated with 20 mg/day vonoprazan (V group) or 20 mg/day esomeprazole (E group) for 8 weeks. We evaluated the 8‐week cure rate for artificial ulcers and any complications after ESD. Results: A total of 80 patients (median age, 73.5 years; 71.3% male) were analyzed. Cure rate for the V group was significantly higher than that for the E group (94.9% [37/39] vs 78.0% [32/41], respectively; P = 0.049). In a multivariate analysis, only vonoprazan was correlated with ulcer healing (odds ratio = 6.33; 95% CI = 1.21–33.20; P = 0.029). Delayed bleeding was experienced only in the E group (7.3% [3/41]), but no significant difference compared with the V group was observed ( P = 0.241). Conclusion: Vonoprazan was significantly superior to esomeprazole for the healing of post‐ESD gastric ulcers and should be considered as a treatment of first choice.